In dubio contra libertatem? O nowelizacji przepisów dotyczących pobytu studentów zagranicznych - Narożniak, Agnieszka (Studia Prawa Publicznego, 2019)
The subject of the paper is the amendment to the Act on Foreigners made in connection with the implementation of Directive (EU) 2016/80. The considerations focus on the provisions according to which a foreigner is refused a visa or a temporary residence permit for the purpose of studying, when there are ‘justified doubts as to the credibility of their statements on the purpose of their stay in the territory of the Republic of Poland, due to evidence or objective circumstances available to the authority, indicating that the purpose of the foreigner’s stay could be different from the declared one.’ The key question is whether the authorities facing some doubts in cases of entry and stay of foreign students should opt for more restrictive solutions and take the opposite direction to the one determined by the formula in dubio pro libertate. The study presents general factual and legal circumstances of the amendment introduced, followed by an attempt to interpret it under substantive law and an analysis of its procedural aspects. The conclusion is that there are no grounds for introducing the principle in dubio contra libertatem in respect of foreign students’ entry and stay. Such understanding of the regulation in question would raise objections as to its compliance with the provisions of Directive 2016/80, which would require the refusal of the right of residence to be based on the evidence established and facts found, with its primary purpose being to facilitate the undertaking of studies by third-country nationals.